Persepsi Siswa Atas Lingkungan Belajar dan Kesiapan Belajar Terhadap Hasil Belajar Ilmu Pengetahuan Sosial - Nurdin Nurdin; Hery Purwosusanto; Tjipto Djuhartono (Jurnal Ilmiah Wahana Pendidikan, 2022)
In The purpose of this study was to determine the effect of students' perceptions on the learning environment and learning readiness. A good learning environment and good student learning readiness are expected to support the teaching and learning process so that learning outcomes are achieved. The research subjects were 80 students at SMA Negeri 4 Tambun . Data collection techniques using a questionnaire. The validity of the data was obtained by testing the validity and reliability, all data had a normal distribution. Data were analyzed using correlation regression. The results of the study prove that students' perceptions of the learning environment have a significant influence on social science learning outcomes. Likewise, learning readiness has a significant influence on social science learning outcomes. The findings also show that students' perceptions of the learning environment and readiness to learn together are less strongly associated with social knowledge learning outcomes.